Promoting workplace psychological wellbeing through Yoga and Tai Chi classes in female university employees - Valdesalici, Alice; Cerea, Silvia; Pecunioso, Alessandra; Paoli, Antonio; Grigolin, Gioia; Nardelli, Rosa; Armenti, Alessandra; Ghisi, Marta (Frontiers in Psychology, 2024)
Introduction Academic environments are known for their high demands, often resulting in significant distress among employees. Thus, identifying effective intervention strategies to mitigate workplace stress is essential. The present study aims to evaluate the potential benefits of mind–body interventions (i.e., Yoga and Tai Chi) on the psychological wellbeing and perceived mental and physical health of female university employees. Methods A total of 166 female university employees and faculty members participated in 10 sessions of Tai Chi or Yoga. They completed self-report questionnaires assessing ruminative thoughts, somatic anxiety, general distress, perceived physical and mental health, and assertive and cooperative behaviors before and after the 10 Tai Chi/Yoga sessions. Additionally, participants completed a state anxiety questionnaire before and after Tai Chi/Yoga second and second-to-last lessons. Results Results showed significant differences between scores pre and post Tai Chi and Yoga programs, with lower ruminative thoughts (p = 0.007), lower somatic anxiety (p < 0.001), and higher perceived mental health (p = 0.038) at the end of the programs (i.e., after 10 sessions) compared to the beginning. Moreover, significant differences were found in state anxiety scores, with a reduction in state anxiety at the end of the second (p < 0.001) and second-to-last (p < 0.001) lessons compared to the start. Conclusion Our findings highlight the potential positive impact of Tai Chi and Yoga programs on the psychological wellbeing and perceived mental health of female university employees. Immediate reductions in state anxiety following single sessions further underscore the potential of these practices for short-term stress relief. Overall, the results support the implementation of mind–body practices in workplace settings to promote a healthier work environment.